2020
DOI: 10.3904/kjim.2020.121
|View full text |Cite
|
Sign up to set email alerts
|

Weight change and microvascular outcomes in patients with new-onset diabetes: a nationwide cohort study

Abstract: Background: Because weight control is important in treatment of type 2 diabetes, it is essential to understand the associations between weight change and the risk of microvascular complications among patients with type 2 diabetes. We examined whether weight changes early after new-onset diabetes have an impact on the clinical outcomes of diabetic nephropathy and retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
(57 reference statements)
0
11
0
Order By: Relevance
“…Hypertension was defined based on diagnostic ICD‐10 codes (I10‐13 or I15) and at least one claim/year for antihypertensive medication or systolic/diastolic blood pressure ≥140/90 mmHg 25 . Dyslipidemia was defined based on diagnostic codes (E78) and at least one claim/year for a lipid‐lowering agent or total cholesterol ≥240 mg/dL 25 , 26 . CVD was defined as diagnostic codes of I21‐22 or I63‐64 25 , 26 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypertension was defined based on diagnostic ICD‐10 codes (I10‐13 or I15) and at least one claim/year for antihypertensive medication or systolic/diastolic blood pressure ≥140/90 mmHg 25 . Dyslipidemia was defined based on diagnostic codes (E78) and at least one claim/year for a lipid‐lowering agent or total cholesterol ≥240 mg/dL 25 , 26 . CVD was defined as diagnostic codes of I21‐22 or I63‐64 25 , 26 .…”
Section: Methodsmentioning
confidence: 99%
“…Dyslipidemia was defined based on diagnostic codes (E78) and at least one claim/year for a lipid‐lowering agent or total cholesterol ≥240 mg/dL 25 , 26 . CVD was defined as diagnostic codes of I21‐22 or I63‐64 25 , 26 . All types of cancer, liver cirrhosis and end‐stage renal disease were also identified using the ICD‐10 codes, and then excluded 25 , 26 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CKD was defined as an estimated glomerular filtration rate (eGFR) <60 mL/min•1.73 m 2 , calculated using the CKD Epidemiology Collaboration (EPI) equation 9 .…”
Section: Definition Of T2dm Comorbidities and Clinical Parametersmentioning
confidence: 99%
“…The body weight fluctuation has been associated with increased cardiovascular events and mortality in the general population and patients with CKD as well as patients with DM [ 7 , 8 , 9 ]. A recent national cohort study found that weight change was associated with increased risks of myocardial infarction (MI), stroke, and death from any cause in people with type 2 DM [ 10 , 11 ], but the effect of weight change on ESRD has not yet been studied in patients with DM.…”
Section: Introductionmentioning
confidence: 99%